Alternatif Model Penanggulangan Pendanaan Kejahatan Terorisme Dengan Stolen Asset Recovery - Yasniar Rachmawati Madjid (Jatiswara, 2016)
This article discuss about prevention of terrorism financing using Stolen Asset Recovery as the alternative model for the prevention. The aims of this aricle to analize excess of Stolen Asset Recovery to prevent financing of Terrorism. This article analyzed using normative juridical approach Statute Conceptual Approach and Approach. There are many obstacles in the implementation of the FATF in combating the financing of terrorism. The first obstacle is the FATF as a watchdog organization that determines which member states must implement the provisions contained in the recommendations given by the FATF. The second obstacle in the FATF recommendation requires immediate asset freeze (freezing without delay) against the alleged perpetrators of crimes that are not appropriate to be applied to the member states to apply the presumption of innocence. Therefore we need an alternative model of another better countermeasures that can be applied and does not interfere with the national interests of member states. There is a body which is a collaboration between the World Bank and the United Nations Office on Drugs and Crime (UNODC) made a model of prevention to help increase a country's development of the prevention of theft of public assets called Stolen Asset Recovery (StAR). StAR has many advantages that the funding models for crime prevention can be adopted to combat terrorist crimes. The advantages include StAR Initiative is done in two ways NCB asset forfeiture and Criminal forfeiture that can be applied in the legal systems are different in each country so that the model is still appreciate the national interest and priority to the country's sovereignty. The second is the StAR Initiative has cooperated so that countries can take the assets of crime in the territory of other countries through specific agreements called Mutual Legal Assistance.